(3eMGSf GdeLGdSs - (3CMeO Hf eMeO Hf ehSi GdUfgGLj GdCfOdSj GdeQj, CHh GdYHGS , GHf GdnYQja,J (B536 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh GdYHGS bO GSJNQJ Gddg JYGdi ai LeY aUhd ef eMGSf GdcdGe hGdeLGdS GdUGOQI Yf Cgd GdEdgGe s
(3BNQgG (B:s
(3aNWhG MHGd eQGSjge hZWh aZWGge hGfWHb JeJ eMGSf GdeLGdS s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B164s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcRjI GdYGeI (B- (3GdehUd (B(1061 (3S(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs